Burnout and associative emotional status and coping style of healthcare workers in COVID-19 epidemic control: A cross-sectional study - Yang, Cece; Wang, Xunqiang; Zhang, Xing; Liu, Wenping; Wang, Chengmin (Frontiers in Public Health, 2023)
Objective To evaluate the prevalence of burnout, clinical anxiety, depression, and insomnia, and estimate the associations of adverse emotional status, coping style and level of self-efficacy with burnout of health care workers in Long-gang District frontline headquarters of COVID-19 epidemic control of Shenzhen, China. Methods In this cross-sectional study, one hundred and seventy-three staff completed the anonymous questionnaires of Maslach Burnout Inventory, PHQ-9, GAD-7, ISI, General Self-efficacy Scale and Simplified Coping Style Questionnaire electronically (https://www.wjx.cn/) in june 2022. Hierarchical logistic regression was used to explore the associated factors of burnout in this study. Results The prevalence of burnout in our participants (defined as high emotional exhaustion or high depersonalization) was 47.40%, and reduced personal accomplishment was 92.49%. The prevalence of clinically significant depression (the cut-off score of ≥ 15), anxiety (the cut-off score of ≥ 10) and insomnia (the cut-off score of ≥ 15) was 11.56%, 19.08% and 19.08% respectively. There was a degree of overlap between burnout and other measures of adverse mental status, most notably for anxiety (odds ratio, 27.049; 95%CI, 6.125-117.732; p<0.001). Hierarchical logistic regression demonstrated that burnout was strongly associated with anxiety (OR=23.889; 95% CI, 5.216-109.414; p<0.001) and negative coping style (OR=1.869; 95% CI, 1.278-2.921; p<0.01) independently. Conclusions Medical staff involved in COVID-19 epidemic control in the post-epidemic era were at high risk of burnout, and most of them were in low personal accomplishment. To reduce anxiety and improve coping style by medical management institutions from the system level may be effective to alleviate burnout of health care workers.